Enhancement or endangerment: a narrative review of pharmacological agents used in the fitness industry - Yogesh Shergin Balakrishnan (International Journal of Basic & Clinical Pharmacology, 2026)
The global fitness industry has witnessed a significant rise in the use of pharmacological agents for enhancement of muscle mass, athletic performance, fat reduction, and physical appearance. Even though regular exercise and balanced nutrition remain the cornerstone of fitness, increasing societal pressure for rapid aesthetic transformation has contributed to the misuse of performance-enhancing drugs (PEDs). This narrative review aims to provide a comprehensive overview of the major pharmacological agents currently used in the fitness industry, including anabolic-androgenic steroids (AAS), selective androgen receptor modulators (SARMs), growth hormone and peptide analogues, stimulants, fat burners, insulin, thyroid hormones, diuretics, and post-cycle therapy drugs. A literature search was conducted using PubMed, Scopus, and Google Scholar databases using relevant keywords related to performance enhancement and fitness pharmacology. Recent evidence from clinical studies, systematic reviews, and regulatory reports were included. Advantages such as increased lean muscle mass, enhanced recovery, improved endurance, and accelerated fat loss were offered by these agents. However, their misuse is associated with serious cardiovascular, endocrine, hepatic, renal, neuropsychiatric, and metabolic complications. The emergence of social media promotion and unregulated online markets has further increased accessibility and misuse, especially among young adults. World anti-doping agency (WADA) and the United States Food and Drug Administration (FDA) continue to issue warnings regarding the safety concerns associated with these substances. This review highlights the pharmacology, benefits, adverse effects, ethical concerns, and public health implications of pharmacological agents used in the fitness industry, emphasizing the urgent need for awareness, regulation, and evidence-based education.